2017
DOI: 10.1002/hbm.23756
|View full text |Cite
|
Sign up to set email alerts
|

The effects of memory training on behavioral and microstructural plasticity in young and older adults

Abstract: Age differences in human brain plasticity are assumed, but have not been systematically investigated. In this longitudinal study, we investigated changes in white matter (WM) microstructure in response to memory training relative to passive and active control conditions in 183 young and older adults. We hypothesized that (i) only the training group would show improved memory performance and microstructural alterations, (ii) the young adults would show larger memory improvement and a higher degree of microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 116 publications
(157 reference statements)
3
53
2
Order By: Relevance
“…Our results suggest that the disparity in findings may reflect underlying neurobiological factors -more precisely, the white matter integrity measured with FA. Indeed, white matter properties have been suggested to contribute to the level of improvement by cognitive interventions (de Lange et al, 2017;Engvig et al, 2012;Mackey et al, 2012) and may also represent one of the brain level targets for the physiological effects of exercise. In the current study, we did exploratory analyses to investigate whether white matter FA has an influence on the relationship between physical performance measures and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that the disparity in findings may reflect underlying neurobiological factors -more precisely, the white matter integrity measured with FA. Indeed, white matter properties have been suggested to contribute to the level of improvement by cognitive interventions (de Lange et al, 2017;Engvig et al, 2012;Mackey et al, 2012) and may also represent one of the brain level targets for the physiological effects of exercise. In the current study, we did exploratory analyses to investigate whether white matter FA has an influence on the relationship between physical performance measures and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Chaddock-Heyman et al, 2013;Gold et al, 2010;Golestani et al, 2014;Mabbott et al, 2006;Nagy et al, 2004;Seghete et al, 2013). Additionally, studies investigating cognitive training suggest that white matter properties also predict the enhancement of cognitive skills after training and that the change in white matter properties following training relates to behavioural improvements (de Lange et al, 2017(de Lange et al, , 2016Engvig et al, 2012;Mackey et al, 2012). Given the suggested relationship of also physical activity and fitness with white matter properties, it is conceivable that white matter has an important role in determining the manner in which physical performance associates with cognitive skills.…”
Section: Introductionmentioning
confidence: 99%
“…While PM training studies provide some support for potentially lasting changes in brain anatomy (see Zatorre et al 2012, Wenger et al 2017, there is limited evidence of such effects in WM training research (see, however, Takeuchi et al 2010, Salminen et al 2016, de Lange et al 2017. As training-related improvements in WM task performance typically decay relatively fast (Melby-Lervåg and Hulme 2013), also modulations of brain activity measured with functional brain imaging can be assumed to mostly reflect temporary…”
Section: Neuronal Plasticity Of Wm and Pm Functionsmentioning
confidence: 99%
“…Nevertheless, brain imaging studies that have accumulated only quite recently (see Table 1) have demonstrated multiple ways how WM training influences brain activity. These include regional changes in a multitude of areas (for a review see Buschkuehl et al 2012, Constantinidis and Klingberg 2016, von Bastian and Oberauer 2014, modulation of anatomical (Takeuchi et al 2010, Salminen et al 2016, de Lange et al 2017) and functional connectivity (Astle , Jolles et al 2013, Takeuchi et al 2013, adapted neuronal firing profiles (Meyers et al 2012), and more efficient neurotransmitter function (Bäckman and Nyberg 2013). As there are limitations in the meta-analysis of behavioral studies, complementary analysis of the brain imaging studies could help in clarifying the mechanisms underlying WM training.…”
Section: Introductionmentioning
confidence: 99%
“…b Plot depicts mean FA change from scan 1 to scan 2 in each group extracted from the significant cluster. Individual subjects' data points are represented by dots in the word learning group, triangles in the active, and squares in the passive control group adult training studies investigating white matter plasticity, a similar junction of crossing fibers including the frontoparietal connection was reported in older adults as a result of memory training (de Lange et al 2017) and multi-domain cognitive training (Cao et al 2016). For the homologue fronto-parietal region in the right hemisphere, a change in FA was reported after reasoning training in young adults (Mackey et al 2012).…”
Section: Discussionmentioning
confidence: 83%